Influences of the perforation on effective transport properties of gas diffusion layers. (November 2018) - Fang, Wen-Zhen; Tang, Yu-Qing; Chen, Li; Kang, Qin-Jun; Tao, Wen-Quan
Highlights: Effective transport properties of reconstructed perforated GDLs are predicted by LBM. A D3Q19 MRT LB model is developed to deal with anisotropic heat transfer. The water distribution in perforated GDL is simulated by two-phase LBM. Effective transport properties of partially saturated GDL are fitted as correlations. The perforated GDL can alleviate the water flood issue. Abstract: In this paper, the through-plane and in-plane effective transport properties, including permeability, diffusivity and thermal conductivity, of the perforated gas diffusion layer (GDL) are predicted using multiple-relaxation-time (MRT) lattice Boltzmann method (LBM) based on stochastic reconstructed microstructures. When predicting effective thermal conductivities of GDL, the effect of anisotropic conductive property of fibers is considered. The effective transport properties of dry perforated GDL are fitted as a function of perforation diameter and porosity. It is found that the permeability and effective diffusivity of GDL increase with perforation diameter and porosity while the effective thermal conductivity decreases. The two-phase LBM is adopted to simulate water distributions in perforated GDLs, and dependences of effective transport properties on saturation are then obtained. The results show that: the existence of the perforation significantly affects the water transport in hydrophobic perforated GDLs if its diameter is larger than the average pore size of GDL. The effective permeability and diffusivity of GDL decrease while effective thermal conductivity increases with saturation. The effective transport properties of perforated GDLs change less significantly with saturation than those of non-perforated GDL if the water droplet intruding into the perforation is displaced, while change more rapidly with saturation if the water droplet remains inside the perforation.